Проектирование теплообменных аппаратов АЭС - Митенков Ф. М. Федор Михайлович; Головко В. Ф. Владислав Федорович; Ушаков П. А. Павел Анатольевич; Юрьев Ю. С. Юрий Сергеевич (Москва, Энергоатомиздат, 1988)
Авторы указаны на обороте тит. листа